Frequency of ehrlichiosis and anaplasmosis in dogs with a history of ticks in a veterinary clinic in Piura, Peru - Naranjo, Natalia (2021)
The objective of the study was to determine the frequency of positive serology for canine erlichiosis (E. canis and E. ewingii) and anaplasmosis (A. phagocitophylum and A. platys) diseases in patients with presence or history of ticks during the period 2017-2018. The sample was composed of dogs who came to consultation to a private veterinary service in the city of Piura-Peru. These patients must have had presence or history of ticks, according to the owners. The information of the clinical signs that were presented at the time of the consultation and that could be compatible with the disease under study were collected in a medical card. Samples of 71 dogs were collected to be analyzed by blood count and a commercial test for the detection of these diseases (SNAP 4Dx- Idexx). It was determined that 55% (39 patients) presented antibodies against Erlichia spp. and 4% (3 patients) Anaplasma sp. All of the patients who presented antibodies against Anaplasma sp. also presented antibodies against Erlichia spp. Among the clinical signs found more frequently in the positive group were lethargy (77%), anorexy (59%), linfoadenomegaly (54%) and fever (49%), without becoming significantly different from the negatives. The only sign more frequent among the negative group was the splenomegaly (49% positive group and 6% negative group). It was determined that the patients with positive serology had alterations in their blood count like anemia (51%), leukocytosis (51%) and thrombocytopenia (54%), while the negative group only got alterations in the white cells. This study reports the serological presence of Anaplasma sp. for the first time and corroborates the presence of Erlichia spp. in the city of Piura.